2007
DOI: 10.1111/j.1365-2710.2007.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of paclitaxel-loaded nanoparticles with radiation on hypoxic MCF-7 cells

Abstract: This work has demonstrated that paclitaxel can be effectively released from a biodegradable PLGA nanoparticle delivery system while maintaining potent combined cytotoxic and radiosensitizing abilities for hypoxic tumour cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…In the previous work, we reported the radiosensitizing effect of paclitaxel-loaded nanoparticles on hypoxic tumor cells (41)(42)(43). Nevertheless, to our knowledge there are no studies on the literature regarding the cytotoxicity of paclitaxel-loaded nanoparticles on hypoxic tumor cells.…”
Section: Introductionmentioning
confidence: 89%
“…In the previous work, we reported the radiosensitizing effect of paclitaxel-loaded nanoparticles on hypoxic tumor cells (41)(42)(43). Nevertheless, to our knowledge there are no studies on the literature regarding the cytotoxicity of paclitaxel-loaded nanoparticles on hypoxic tumor cells.…”
Section: Introductionmentioning
confidence: 89%
“…However, the possibilities of controlling the NO release can be widened using also other drug delivery systems (DDS), such as microparticles. Microparticles have been used as drug delivery systems because they offer advantages such as a high stability, easy uptake into the cells by endocytosis, and targeting ability to specific tissues or organs by adsorption or coating with ligand materials at the surface of the particles [61][62][63][64][65][66][67]. Many biodegradable polymers are appropriate for making microparticles.…”
Section: Trans-½ruðnoþðnhmentioning
confidence: 99%
“…37,39,41 In a previous study, we reported the radiosensitizing effect of paclitaxel-loaded nanoparticles on hypoxic MCF-7 cells. 31 Nevertheless, to our knowledge there are no reports on the literature regarding the cellular uptake of paclitaxel PLGA nanoparticles.…”
Section: Research Papermentioning
confidence: 99%
“…23,24 Some studies on the use of nanoparticles as carriers for paclitaxel have been published. [25][26][27][28][29][30][31] Recently, paclitaxel has been reported to be successfully encapsulated in the pyromellitylimidoalanine-1, 6-bis(carboxy-phenoxy)hexane (PMA-CPH), PLGA microspheres and micellar nanoparticles as a radiosensitizer. 37,39,41 In a previous study, we reported the radiosensitizing effect of paclitaxel-loaded nanoparticles on hypoxic MCF-7 cells.…”
Section: Research Papermentioning
confidence: 99%
See 1 more Smart Citation